What Do Football Players Look at? An Eye-Tracking Analysis of the Visual Fixations of Players in 11 v 11 Elite Football Match Play - Aksum, Karl Marius; Magnaguagno, Lukas; Bjørndal, Christian Thue; Jordet, Geir (Frontiers in Psychology, 2020)
Current knowledge of gaze behavior in football has primarily originated from eye-tracking research in laboratory settings. Using eye tracking with elite players in a real-world 11 versus 11 football game, this exploratory case study examined the visual fixations of midfield players in the Norwegian premier league. A total of 2832 fixations by five players, aged 17–23 years (M = 19.84), were analyzed. Our results show that elite football midfielders increased their fixation duration when more information sources became available to them. Additionally, participants used shorter fixation durations than previously reported in laboratory studies. Furthermore, significant differences in gaze behavior between the attack and defense phases were found for both areas of interest and fixation location. Lastly, fixation locations were mainly on the ball, opponent, and teammate category and the player in possession of the ball. Combined, the results of this study enhance the knowledge of how elite footballers use their vision when playing under actual match-play conditions. They also suggest that laboratory designs may not be able to capture the dynamic environment that footballers experience in competition.